Malays and time: flexibility - Harun, Nur Syikri; Ismail, Fathiyah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Time’s a finite resource, definitely. We have day light and night. They all count for 24 hours, which’re our daily capital. How time’s spent depends on individuals. Some people have it well-spent in a productive way, which’s worth the time, but many have it squandered and wasted, disappearing into thin air. But the time I’m talking about has nothing to do with frequencies, for instance, “How many times we’ve met?”. Don’t get confused with ‘thyme’, too. It’s all about the clock that’s ticking and the time that’s running.